Empowering Local Communities Through the Innovative Development of Sacha Inchi Leaf Tea in Badak Village - Arrazaqia, Fatihah; Amirin, Thabathabia Asyam Labib; Maharani, Syerline Aning; Nurrizki, Dyanti Arisa; Zain, Rifqi Akmal; Raihan, Ammar Adi; Utami, Sahrina Putri; Nuriyah, Ike; Tarissa, Maydelvis Putri; Sugiarti, Sugiarti; et al. (Proceedings Series on Social Sciences & Humanities, 2025)
This study presents a community empowerment program in Badak Village, Pemalang Regency, Central Java, focusing on processing Sacha Inchi (Plukenetia volubilis L.) leaves into herbal tea. Using the Asset-Based Community Development (ABCD) approach, the initiative trained local farmers and women’s groups to produce tea combining Sacha Inchi leaves, Stevia rebaudiana, and Jasminum sambac, processed with two drying methods—controlled oven drying (120°C and 140°C) and natural sun drying. The program included harvesting, washing, cutting, drying, mixing, and packaging into tea bags, followed by sensory evaluations of aroma, color, and taste by 21 participants. Results indicated that high-temperature oven drying (140°C) produced a stronger flavor and aroma preferred by some consumers, while low-temperature oven drying (120°C) yielded a milder taste, and sun-drying resulted in a lighter flavor and brighter color. These findings highlight the influence of drying methods on sensory quality, offering valuable insights for product development to match consumer preferences. The program demonstrates that integrating local resources with value-added processing can enhance rural livelihoods, promote sustainable agriculture, and support the commercialization of functional herbal beverages.